Biochemical profile differences during the transition period based on different levels of non-esterified fatty acids at 7 weeks before parturition in Mediterranean Italian dairy buffaloes (Bubalus bubalis) - Lisuzzo, Anastasia; Mazzotta, Elisa; Cappelli, Giovanna; Martucciello, Alessandra; Monteiro, Bruno Moura; Sales, José Nélio Sousa; Di Vuolo, Gabriele; De Donato, Immacolata; Schiavo, Lorena; De Carlo, Esterina; Rossi, Pasquale; Contiero, Barbara; et al. (Frontiers in Veterinary Science, 2024)
Metabolic adaptations to negative energy balance as lipomobilization influence inflammatory responses, immune function and oxidative stress in animals. The aim of this study was to evaluate the biochemical profile of Mediterranean buffaloes with different levels of lipomobilization from prepartum to postpartum period. Seventy-six Mediterranean Buffaloes were enrolled, and a weekly blood sample was taken from 7 weeks before to 6 weeks after calving. The concentration of nonesterified fatty acids (NEFA) was determined in serum and used to detect buffaloes at 7 weeks before calving into: mild (NEFA-I; NEFA≤0.29 mEq/L; n=18), medium (NEFA-II; 0.290.29 mEq/L; NEFA-II and NEFA-III) at seven weeks before calving should be monitored more closely to reduce the risk of metabolic diseases. Furthermore, the medium (NEFA-II) and severe (NEFA-III) lipomobilization groups could be associated to a different animals' ability to handle the metabolic status. The severe mobilization was most associated with a greater energy deficit in both prepartum and postpartum periods without oxidative stress. On the contrary, the medium mobilization was associated with a less severe energy deficit, and an inflammatory status and oxidative stress during the prepartum period.